Exporting and workforce skills-intensity in the Egyptian manufacturing firms: Empirical evidence using world bank firm-level data for Egypt - Ahmed Fayez Abdelgouad (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2016)
The World Bank's Enterprise Surveys (WES( for the manufacturing firms in Egypt are used to study the characteristics of exporting firms and the determinants of the exporting behavior in the Egyptian manufacturing sector in general and to investigate the link between the exporting activities and the workforce skills-intensity in the Egyptian manufacturing sector in specific. Several methods to estimate the probability and intensity of exporting are presented. The main findings indicate that firms in the manufacturing sector in Egypt which their workforce are characterized by higher levels of skills-intensity are more likely to export compared to other firms with lower levels of skills-intensity. Firms that hire female workers are more likely to export than other firms which do not employ women. Furthermore, firms that are larger in their size, have R&D departments, and owned by foreigners are more likely to export than others and have statistically significant effects on export intensity as well. The results suggest also that firms that are larger in their size are more likely to start to export than others.
Keywords: J24; F14; F16; 330; Exporting; Workforce skills; World Bank Enterprise Surveys; Egypt; Manufacturing